Evaluasi Tingkat Kepuasan Penyelenggaraan Kejuaraan Kota Taekwondo Surabaya Tahun 2025 melalui Metode Service Quality - Chamelia Tsany Septihandari; Awang Firmansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The implementation of the Surabaya Taekwondo City Championship 2025 is an opportunity to measure the success of sports events at the regional level, especially Surabaya City. This study aims to analyze the level of satisfaction of participants and visitors to the implementation of the 2025 Surabaya Taekwondo City Championship using the Service Quality (ServQual) method, which includes Physical Evidence (Tangibles), Reliability, Responsiveness, Assurance, and Empathy using quantitative research methods with a survey approach. Data were collected through questionnaires which distributed to coaches and guardians of championship students in Surabaya. The sampling technique used the Proportionate Stratified Random Sampling method with a total of 243 respondents. The data analysis technique uses a Likert scale which is then processed with SPSS software. The results showed that all dimensions of Service Quality have a high level of validity and are strongly correlated with visitor satisfaction. In general, the championship received a good assessment, especially in the aspects of service reliability and assurance. However, there are several aspects that need to be improved, such as facility comfort, committee communication effectiveness, and responsiveness to visitor complaints. The conclusion of this study is that the implementation of the 2025 Surabaya Taekwondo City Championship has met the satisfaction standards of participants and visitors, although there are still several aspects that need to be improved. Therefore, it is necessary to improve the quality of facilities, optimize committee communication, and strengthen the security system and services.